Is unilateral lower leg orthosis with a circular foot unit in the treatment of idiopathic clubfeet a reasonable bracing alternative in the Ponseti method? Five-year results of a supraregional paediatric-orthopaedic centre - N. Berger; D. Lewens; M. Salzmann; A. Hapfelmeier; L. Döderlein; P. M. Prodinger (BMC Musculoskeletal Disorders, 2018)
Abstract Background In the Ponseti treatment of idiopathic clubfoot, children are generally provided with a standard foot abduction orthosis (FAO). A significant proportion of these patients experience irresolvable problems with the FAO leading to therapeutic non-compliance and eventual relapse. Accordingly, these patients were equipped with a unilateral lower leg orthosis (LLO) developed in our institution. The goal of this retrospective study was to determine compliance with and the efficacy of the LLO as an alternative treatment measure. The minimum follow-up was 5 years. Results A total of 45 patients (75 ft) were retrospectively registered and included in the study. Compliance with the bracing protocol was 91% with the LLO and 46% with the FAO. The most common problems with the FAO were sleep disturbance (50%) and cutaneous problems (45%). Nine percent of patients experienced sleep disturbance, and no cutaneous problems occurred with the LLO. Thirteen percent of patients being treated with an FAO until the age of four (23 patients; 40 ft) underwent surgery because of relapse, defined by rigid recurrence of any of the components of a clubfoot. Fourteen percent of patients being treated with an LLO (22 patients; 35 ft), mostly following initial treatment with an FAO, experienced recurrence. Conclusion Changing from FAO to LLO at any point during treatment did not result in an increased rate of surgery and caused few problems.